Manakah yang Benar: Mikroekonomi atau Ekonomi Mikro - Rosida Tiurma (Bina Ekonomi, 1999)
This paper discusess the writing of words originating from foreign languages in Bahasa Indonesia. Description analysis is used as a method in this paper and example words are taken from newspapers and magazines since many faults in writing the absorbed words are usually found in those two sources. The paper reviews the writing of the absorbed words from morphology (forms) and semantics (meaning) aspects. The review will give a clear and detail description in writing absorbed words in Bahasa Indonesia, especially for economic terms.